MUNC Revolution Good Practice Guide. - Dinnen, Mark; Judd, Madelaine-Marie; Lingham, Nicole; Carter, Matthew; Mau, Vandy; Bellamy, Alex; Trood, Russell; Kinash, Shelley; Richardson, Brittany (Office for Learning and Teaching, 2016)
Final report from a project which explored Model United Nations Conferences as an employability skills solution for Learners. SHOC is a simulation program, created by the project team, which illustrates the rate and spread of an infectious disease pandemic. The project team proposed that participating in technology-enhanced MUNC with SHOC would improve learners' skills in: engaging with world issues, thinking spontaneously, communicating with confidence and authority, interpreting and responding to digital information, and contributing appropriately to group process and mentoring / being mentored by others. These technology enhanced MUNCs were run and operated at two universities, including high school and undergraduate students as delegates. The research approach of the project was design based, pre and post testing the undergraduate students' self and peer ratings of these skills. In addition, full transcripts of the MUNC process were qualitatively analysed for themes and evidence of skill development.